O direito ao planejamento tributário na Constituição Federal - Boicenco, Rubens (2020)
The present study aims to analyze tax planning in Brazil from the Brazilian Federal Constitution perspective, seeking to identify the principles that support the right of taxpayers to, in view of certain lawful objectives, plan their activities with lawful practices so as not to incur in the event of incidence of a tax rule or to incur in the event of incidence of a less onerous tax rule. From this perspective, the theories that aim to restrict such right to tax planning and its origins in foreign Acts will be analyzed, as well as the types of anti-avoidance rules that aim at its implementation, in order to identify the limits of application of such theories and anti-avoidance rules in Brazil. Then, the Brazilian experience will be verified through the issuance of anti-avoidance rules Acts and through the application of such theories in administrative tax legal proceedings as well as in Brazilian Court, seeking to verify the adherence of such experiences to the Brazilian Federal Constitution rules